Seismic Evaluation of Existing Wharf Structures Subjected to Earthquake Excitation: Case Study - Doran, Bilge; Shen, Jay; Akbaş, Bülent (Earthquake Engineering Research Inst, 2015)
The ability of aging shore structures to resist design seismic forces located in high-seismicity regions has been a subject of interest for many researchers. Seismic design codes have become more stringent and suggest the use of new design methods, such as performance-based design. According to the Turkish Code for Shore Structures (TCSS 2008), a pile-wharf structure is expected to withstand a D1 level of ground motion (corresponding to a return period of 72 years) with minor or no damage and a D2 level of ground motion (corresponding to a return period of 475 years) with short-term loss of serviceability. In this study, nonlinear static analyses of the seismic performance of two existing pile-wharf structures were performed (pushover analyses) according to TCSS (2008). The results are presented here.
Keywords: Performance